Elucidating the structures and cooperative binding mechanism of cesium salts to the multitopic ion-pair receptor through density functional theory calculations1. Issue 35 (21st September 2015) - Sadhu, Biswajit; Sundararajan, Mahesh; Velmurugan, Gunasekaran; Venuvanalingam, Ponnambalam
<x xml:space="preserve">Abstract</x> Quantum chemical studies predict the binding of Cesium salts to multitopic ion-pair receptor is through cooperative mechanism.